Adverse events after surgery for injuries to the subaxial cervical spine: analysis of incidence and risk factors - Raisch, Philipp; Pflästerer, Jan; Kreinest, Michael; Vetter, Sven Y.; Grützner, Paul Alfred; Jung, Matthias (European journal of trauma and emergency surgery, 2024)
To determine the incidence of severe surgical adverse events (sSAE) after surgery of patients with subaxial cervical spine injury (sCS-Fx) and to identify patient, treatment, and injury-related risk factors.